Fundamental ideas of stochastics in primary education textbooks: Teaching alternative - López Mojica, José Marcos; Ojeda Salazar, Ana María; Salcedo Prado, Jesús (IE Revista de Investigación Educativa de la REDIECH, 2018)
In the Mexican National Education System, probability and statistics are the most neglected disciplines, despite being important in the solution the problems of daily life. The number cult prevails, which limits the development of probabilistic and statistical thoughts. The objective of this document is to identify the fundamental ideas of stochastic in the textbook lessons of the first cycle (first and second grades) of primary education in Mexico and to demonstrate that these convene a conceptual network. The previous thing would allow its introduction in the classroom on the part of the teachers. Under an epistemological approach, criteria of analysis were used to indicate the ten fundamental ideas of Stochastics and the epistemological nature of the appropriation of the mathematical concept. The results concern to point out an absence of the subjects of probability and reduction of the subjects of statistics to the mere numerical calculation in the textbooks. No lesson refers to the Stochastics in a stated way, but despite this, seven could be rescued that imply a random phenomenon and its possible treatment in the classroom in a systematic way.